The forum is open now - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Valorisation d expériences: Forum européen sur la coopération au développement rural, Montpellier, France, September 2002 CTA/Inter-Réseaux, Paris, 2002. CD-ROM CTA number 1099. 20 credit points